Inflammatory bowel disease and Clostridium difficile infection: contrasting views of international clinical professionals - Stallmach, Andreas; Anttila, Veli-Jukka; Hell, Markus; Gwynn, Simon; Merino-Amador, Paloma; Petrosillo, Nicola; Ráčil, Zdenek; Warren, Tim; Wenisch, Christoph; Wilcox, Mark (Zeitschrift für Gastroenterologie, 2018)
Introduction In patients with inflammatory bowel disease (IBD), Clostridium difficile infection (CDI) is a risk factor for both morbidity and mortality. Currently, appropriate management is unclear. Guidance on best practice in the diagnosis and treatment of CDI in IBD patients is therefore needed.Methods A multidisciplinary group of clinicians involved in the treatment of patients with IBD and CDI developed 27 consensus statements. Respondents were asked to rate their agreement with each statement using a 4-point Likert scale. A modified Delphi methodology was used to review responses of 442 physicians from different specialties (including infectious disease specialists [n = 104], microbiologists [n = 95], and gastroenterologists [n = 73]). A threshold of 75 % agreement was predefined as consensus.Results Consensus was achieved for 17 of the 27 statements. Unprompted recognition of risk factors for CDI was low. Intensification of immunosuppressive therapy in the absence of clinical improvement was controversial. Clear definitions of treatment failure of antibiotic therapy in CDI and recurrence of CDI in IBD are needed. Respondents require further clarity regarding the place of fecal microbiota transplantation in CDI patients with IBD. Differences were observed between the perceptions of microbiologists and gastroenterologists, as well as between countries.Conclusions Different perceptions both between specialties and geographical locations complicate the development of an internationally accepted algorithm for the diagnosis and treatment of CDI in patients with IBD. This study highlights the need for future studies in this area.
Keywords: Chronisch-entzündliche Darmerkrankung; Clostridium difficile Infektionen; Konsensbericht